RUH, NAFS, AKAL, QOLB, DAN FITRAH SEBAGAI POTENSI DASAR MANUSIA DALAM PENDIDIKAN ISLAM - Abdullah Abdullah; Siti Rohimah (Jurnal Syaikh Mudo Madlawan: Kajian Ilmu-Ilmu Keislaman, 2026)
This study aims to analyze ruh, nafs, aql, qalb, and fitrah as basic human potentials in Islamic education and their role in forming human beings as servants of Allah. This research uses a qualitative approach with a library research method. The data were obtained from books, scientific articles, and relevant academic sources related to Islamic education, Islamic psychology, and the philosophy of Islamic education. The data were analyzed using content analysis and descriptive-conceptual analysis by identifying, classifying, and synthesizing the meanings and educational implications of the five human potentials. The results show that ruh functions as the source of spiritual awareness, nafs as the inner impulse that requires purification and control, aql as the intellectual potential to understand truth, qalb as the center of faith and moral consciousness, and fitrah as the natural tendency toward tauhid and goodness. These five potentials are interrelated and should be developed integratively through Islamic education. The study concludes that Islamic education must not only emphasize intellectual achievement, but also spiritual formation, moral development, self-control, and preservation of human nature. Therefore, the integration of ruh, nafs, aql, qalb, and fitrah can serve as a conceptual foundation for forming faithful, knowledgeable, morally responsible, and spiritually conscious servants of Allah.